Разделение потока в спиральной камере центробежной турбомашины - Гапон, Галина Александровна (НТУ "ХПИ", 2011)
Flow in a spiral chamber of a centrifugal turbomachine is investigated on the basis of the dynamics equations of variable mass continuum. The analytical representation of the parameters averaged over the cross-section area is obtained. The analytical expression for finding the cross-section in which the stream splitting take place is also obtained. The derived formulas establish dependences of the influence of the operating conditions and the conditions on the inlet and outlet of the flow on the flow characteristics. The applicability of 1D model to calculate the parameters of three-dimensional flow is discussed. A comparison of the results of the 1D model and 3D calculation by FLUENT-6 is performed. It is shown that the results of 1D calculations give qualitatively the same flow parameters behavior as the results of 3D simulation.
Keywords: энергетическое оборудование; энергосбережение; вентиляторы; машины тягодутьевые